Assessment of health-related quality of life among outpatients with asthma at Hue University of Medicine and Pharmacy Hospital - Vo, Thi Hong Phuong; Nguyen, Thi Ngoc Quyen; Ngo, Thi Kim Cuc; Phan, Dang Thuc Anh; Hoang, Thi Lan Huong; Nguyen, Phuoc Bich Ngoc (Tạp chí Y Dược Huế, 2023)
Background: Asthma is either a chronic respiratory disease or a serious global health problem that is common in all ages at a high rate. It seriously affects not only the physical health but also the health-related quality of life (HRQoL) of patients. Objectives: (1) To determine HRQoL score among asthmatic outpatients at Hue University of Medicine and Pharmacy Hospital; (2) To assess factors associated with HRQoL among asthmatic outpatients at Hue University of Medicine and Pharmacy Hospital. Subjects and methods: A descriptive cross-sectional study was conducted on 102 asthmatic outpatients at Hue University of Medicine and Pharmacy Hospital by using a self-administered questionnaire. Results: The male-to-female patient ratio was 1.68/1. The mean age of study participants was 59.2 ± 15.39 (26-95). A large number of patients were unemployed (55.9%) and had a low education level (54.9%). Participants with comorbidities and time of being diagnosed with asthma over 10 years accounted for the highest percentage, 69 .6%, and 48.0% respectively, but most patients were not hospitalized due to an acute asthma attack within the past year (88 .2%). The most common type of inhaler being used was DPI or the combination of MDI and DPI (35.3%) whereas the prevalence of patients only using the Metered-Dose Inhalers (MDI) was 29.4%. There were 40.2% of patients who were severely affected. The mean value of the total HRQoL score was 4.27 ± 0.747. The domain that most impacted HRQoL was “Activity limitations” whereas “Symptoms” affected the least. Men had higher HRQoL than women (6.441 times); The participants who did not have asthma-related family history were likely to have better HRQoL than others (3.3 times); The patients who used MDI or DPI alone had higher HRQoL scores than the group used the combination of two devices (2.788 times). Conclusions: Asthma remarkably affected asthmatic patients’ quality of life. The factors associated with HRQoL were gender, family history of asthma, and the type of inhaler.